Solar Energetic Electron Spectra Measured with Solar Orbiter - Fedeli, Annamaria (My University, 2022)
The Sun produces eruptive events that release protons, electrons as well as heavier nuclei (e.g. He-Fe) into the heliosphere. These particles are accelerated up to relativistic energies in at least two distinct processes, i.e., solar flares and shocks driven by coronal mass ejections (CMEs) or their interplanetary counterparts (ICMEs). Particles in the interplanetary (IP) space are known as solar energetic particles (SEP). The energy spectrum of SEPs contains the footprint of the acceleration process. The spectrum can, however, be disrupted by transport effects. In this thesis we study the energy spectrum of solar energetic electrons (SEE) measured by the Energetic Particle Detector (EPD) on board the Solar Orbiter (SolO) spacecraft. We use the orthogonal distance regression (ODR) to fit the spectrum of 43 SEE events observed between November 2020 and March 2022. We fit the spectrum with four different mathematical models used in previous studies: a single power-law, a single power-law with an exponential cutoff, a broken power-law and a broken power-law with an exponential cutoff. We then choose the best model to describe each event. The broad energy range of EPD (25-475 keV) allows us to conduct a detailed analysis of the spectra and investigate the possible presence of separate spectral breaks and their relationship to two specific transport effects, for example Langmuir wave generation and pitch-angle scattering. In order to study whether the SEE spectra have more than one break we employ an indirect method of restricting the energy range used in the fits to the separate instruments or combinations of instruments of EPD. The combinations of instruments used in our analysis are STEP (2-80 keV), EPT (25-475 keV), STEP+EPT (2-475 keV) and EPT+HET (25 keV-30 MeV). We compare our results to previous observational and modeling studies that discuss the presence and underlying mechanism of different spectral breaks. We found strong evidence of the presence of two distinct spectral breaks at ~20 +/- 13.2 keV and ~70.0 +/- 30.5 keV. We also found evidence that the lower energy spectral break is caused by Langmuir wave generation. We could not, however, find the expected dependencies for the higher break in terms of pitch-angle scattering.
Keywords: Solar Energetic Particles, Solar Energetic Electrons, Energy Spectra, Spectral Break, Spectral Index, Transport Effects, Pitch-Angle Scattering, Langmuir Wave Generation.